H3K18Ac as a Marker of Cancer Progression and Potential Target of Anti-Cancer Therapy - Marta Hałasa; Anna Wawruszak; Alicja Przybyszewska; Anna Jaruga; Małgorzata Guz; Joanna Kałafut; Andrzej Stepulak; Marek Cybulski (Cells, 2019)
Acetylation and deacetylation are posttranslational modifications (PTMs) which affect the regulation of chromatin structure and its remodeling. Acetylation of histone 3 at lysine placed on position 18 (H3K18Ac) plays an important role in driving progression of many types of cancer, including breast, colon, lung, hepatocellular, pancreatic, prostate, and thyroid cancer. The aim of this review is to analyze and discuss the newest findings regarding the role of H3K18Ac and acetylation of other histones in carcinogenesis. We summarize the level of H3K18Ac in different cancer cell lines and analyze its association with patients’ outcomes, including overall survival (OS), progression-free survival (PFS), and disease-free survival (DFS). Finally, we describe future perspectives of cancer therapeutic strategies based on H3K18 modifications.